Specific gravity of Ludai (Sapium baccatum) according to height level and distance from pith / Ahmad Zaki Mohamed Hashim - Mohamed Hashim, Ahmad Zaki (2002)
Specific gravity (SG) of Ludai (Sapium baccatum) was determined using the water displacement method. The specimens used are from three different parts of the tree that is, base (DBH), middle (50% of clear bole height) and top (80% from DBH). The study showed the differentiation of SG of Ludai at different height level. Beside that the effect of SG at different distance from pith are also found. The average specific gravity value is 0.304. It has the highest specific gravity value at the middle part of the tree and nearest specimen to the bark. It is directly related to density, therefore it has opposite relation with moisture content. Thus many more research on Ludai should be performs as it can increase the usage of this non-commercial species in wood industries.